PEMBENTUKAN AKHLAK SISWA (Studi Kasus Di SMPN 03 Pujon Satu Atap) - Akhis Ilmaya Shofa; Moh Muslim; Bahroin Budiya (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study aims to determine the implementation of the moral formation of students at SMPN 03 Pujon Satu Roof. This study uses a qualitative approach by examining social phenomena in an atmosphere that takes place naturally or naturally. The researcher acts as an observer in moral formation at SMPN 03 Pujon Satu Roof. The research instrument used is by using data collection techniques, interviews, and observations in the process of learning to read yasin, as well as through observation, interviews and documentation. Based on the results of the interview, it was found that the formation of morals towards oneself at SMPN 03 Pujon Satu Roof. this is good, it can be seen from the formation of morals by reading the Koran before entering class, praying dhuha in congregation, making disciplinary rules, giving punishments for those who violate. The formation of morals towards teachers needs to be improved with better steps, because with good morals students will respect teachers. Moral formation towards older and younger people states that teachers at SMP 03 Pujon Satu Atap have educated their students to always respect older people. Moral formation. The formation of morals towards the environment / the surrounding environment proves that SMPN 03 PUjon Satu Roof has good steps in forming morals in schools.